Viral etiology of acute respiratory infections in Sub-Saharan Africa during the pre-COVID-19 period (2006–2019): a systematic review and meta-analysis - Kaboré, B.W.O.; Gouba, N.; Ilboudo, Abdoul K.; Lingani, M.; Savadogo, M.; Ouedraogo, E.; Cissé, A.; Simonis, V.; Tarnagda, Z. (BioMed Central, 2025)
Objective: This systematic review and meta-analysis aimed to estimate the prevalence of respiratory viruses among people with acute respiratory infections (ARI) in Sub-Saharan Africa.